Plastic Surgery in the Multimodal Treatment Concept of Soft Tissue Sarcoma: Influence of Radiation, Chemotherapy, and Isolated Limb Perfusion on Plastic Surgery Techniques - Kapalschinski, Nicolai; Goertz, Ole; Harati, Kamran; Kueckelhaus, Maximilian; Kolbenschlag, Jonas; Lehnhardt, Marcus; Hirsch, Tobias (Frontiers in Oncology, 2015)
Surgical intervention is the mainstay treatment for soft tissue sarcomas. The significance of adjuvant and neoadjuvant therapies such as chemotherapy, radiation and isolated limb perfusion remains under controversial discussion. The goal of this review is to discuss the effects of the aforementioned treatment modalities and their timing of application on plastic surgery techniques. Furthermore, options of reconstruction in cases of complications caused by adjuvant and neoadjuvant therapies are discussed. When compared with adjuvant radiation, neoadjuvant treatment can reduce negative side effects such as fibrosis and edema, because radioderma can be removed during the subsequent surgical procedure. Furthermore, there have not been any reports of negative effects of neoadjuvant radiation on microsurgical procedures. However, the dose of neoadjuvant radiation correlates with increased risks of impaired wound healing postoperatively. Thus, a patient-specific approach to decide whether radiation should be performed adjuvant or neoadjuvant is necessary. Pre-operative irradiation should be considered in cases where functional structures are exposed after tumor resection, in order to ensure the best possible functionality. Adjuvant radiation should be considered in all other cases because of its known superior wound healing. . As for chemotherapy, no negative influence of its use adjuvant or neoadjuvant to reconstructive procedures such as local or free flaps has been reported. Lastly, small sample size studies have not shown increased risks of microsurgical failure or wound complications after isolated limb perfusion. The findings of this review suggest that the chronological order of the discussed therapeutic approaches is not a decisive factor in the surgical outcome of reconstructive procedures for soft tissue sarcoma.